Music and spatial injustice in banlieue cinema. Issue 3 (1st October 2020) - McNeill, Isabelle
ABSTRACT: This article examines the use of pre-existing music in French films set in impoverished banlieue neighbourhoods. It draws on Dikeç's concept of 'spatial injustice', which arises in a convergence of media representation and government policy, entrenching inequality, in the context of the 'fracture coloniale' in French society. Pre-existing music, with its wider spheres of signification beyond the film, potentially disrupts reifying visions of the banlieue . The article considers 'third space music', applying Powrie's concept to contemporary cinema in the banlieue . For context, Le Thé au harem d'Archimède (Mehdi Charef, 1985) and La Haine (Mathieu Kassovitz, 1995) show pre-millennial banlieue films using music as a shared cultural resource. La Haine begins to evoke a third space by foregrounding analogue 'sampling', a hip-hop practice in which dominant codes are appropriated and reconfigured, an aesthetics which now pervades contemporary digital life. Looking at pre-existing music in more recent films Divines (Houda Benyamina, 2016) and Swagger (Olivier Babinet, 2016), through the prism of 'third space music' and sampling, shows how these films use music in their search for alternative ways of representing the over-determined space of the banlieue, whilst also confronting its spatial injustice.